ANALISIS HUBUNGAN KAUSALITAS ANTARA EKSPOR DAN PERTUMBUHAN EKONOMI INDONESIA PERIODE 1996 – 2016 - Danny Jaya Halim (CALYPTRA, 2018)
This study investigates the causal relationship between GDP and export in Indonesia for the period of 1996 to 2016. This study used a quantitative approach based on Granger causality. The data used are secondary data obtained from World Bank. This research use statistical test including unit root test, Johansen cointegration test, and Granger causality test. Research findings indicate one way causality from export to GDP, and supports the export-led growth hypothesis. The unit root test indicates that both of data are integrated or stationary at the same level (first difference), each data are stationary at the critical value 5% and 1%. Granger causality test indicates a one way causality relationship on short-term from export to GDP at the significance level 10%, and no causal relationship between both variables on long-term. Results indicate that there is one way causality relationship from export to GDP, which means that export affects GDP positively, growth on export will affect GDP positively. In order to raise GDP government should attempt to apply more trade policy that supports export growth.